Changes in hydro-electrolytic parameters among a basketball team players during the 4th Benin University games. - Bio Nigan, Issiako; TONON, Brigitte Affidéhomé; Gouthon, Polycarpe; Houngbédji, Sylver J.; FALOLA, Jean-Marie; Bio Nigan, Raïmath Y. T (My University, 2013)
This prospective study has been undertaken to determine the extent of the hydro-electrolytic changes during the Benin University Games (BUG) among student basketball players of the National Institute of Youth, Physical Education and Sport. Body weight, the Urine Specific Gravity (USG), drunk water, the electrolytes (Na+, K+, Na/K ratio) of 10 student players (26.5 ± 5.8 years; 181.4 ± 8.3 cm; 75.0 ± 11.3 kg) have been measured before and at the end of the first, second, and fourth matches played for five days before 10: 00 a.m. The weight loss was around 1.8% for the first two matches and 2.2% for the fourth. Before the first match, six players were dehydrated (USG > 1.020) and at the end of the fourth one, they were seven. Urinary Na+ decreased up to 42.8% at the end of the fourth match, as well as urinary K+ whose value was four times lower at the end of the fourth match than that of the first. The weight loss was important in these student basketball players during their matches played outdoors in the morning. Since they were in majority dehydrated prior to the competition, they may benefit from a counsel program on hydration strategies during recovery, in order to reduce the risk of dehydration.
Keywords: Basketball; Competition; Hot environment; Dehydration; Electrolytes.